EFFECTS OF A CHANGING ORGANIZATIONAL ECOLOGY ON RACIAL DISPARITIES IN INFANT MORTALITY. Issue 6 (August 2015) - Sparks, Shannon M. A.; Faust, Victoria; Christens, Brian D.; Hilgendorf, Amy E.; Boyd, Neil
<x xml:space="preserve">Abstract</x> For a seven‐year period, the disparity in birth outcomes between Blacks and non‐Hispanic Whites in one Wisconsin county closed for reasons not epidemiologically explainable. Examination of the ecology of organizations offered promise for considering the environmental factors influencing African American mothers and birth outcomes during this time. Qualitative analysis of interview data from representatives of health, social service, and advocacy organizations in the county focused on three themes: organizational and network change, organizational philosophies and orientations, and organizational coordination and competition. Results suggest that organizations collaborated variably during this time as adaptations to a changing ecology of funding, political influence, and dominant philosophical orientations. Peak levels of organizational collaborations fostered systems‐level orientations to relational, community‐centered work and coordinated, holistic service provision for underserved mothers and families. Ecological factors promoting collaboration among organizations, and the development of an interorganizational collaborative in particular, influenced further system changes with implications for birth outcomes. Additional analyses discuss systems‐level implications for interorganizational endeavors from the lens of organizational ecology.